2020
DOI: 10.32598/jhnm.30.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Lecturing and Tabletop Exercise Methods on Level of Preparedness of Nurses against Natural Disasters

Abstract: Hospitals are the first-line care providers in natural disasters. Nurses, as one of the critical health professional groups, require adequate peroration for responding to natural disasters. Due attention has to be paid to various teaching methods to improve the level of nurses' preparedness. Objective: This study compared the effect of lecturing and lecturing-tabletop exercise methods on the level of nurses' preparedness against natural disasters. Materials and Methods: In this quasi-experimental study, 74 nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…We speculate that this design will increase the efficiency of training programs. In a study that compared the effect of disaster response training based on lectures vs. tabletop exercises, Mirzaei [21] reported that although knowledge scores improved after training in both groups, the group that was trained using the tabletop exercise, as well as the lecture, scored higher than the group that received the lecture only. Thus, an approach based on both lectures and tabletop exercises enhances the efficiency of education/training of responses to emerging infectious diseases and should be considered when designing training programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that this design will increase the efficiency of training programs. In a study that compared the effect of disaster response training based on lectures vs. tabletop exercises, Mirzaei [21] reported that although knowledge scores improved after training in both groups, the group that was trained using the tabletop exercise, as well as the lecture, scored higher than the group that received the lecture only. Thus, an approach based on both lectures and tabletop exercises enhances the efficiency of education/training of responses to emerging infectious diseases and should be considered when designing training programs.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study [23], the performance of infection control for emerging infectious diseases was better in nurses who received two or more training sessions on emerging infectious diseases and PPE than in nurses who did not receive such training and in nurses who received repeated training during an outbreak than in nurses who did not. Mirzaei [21] found that the level of nurses' knowledge regarding disaster responses had decreased by 4 weeks after as compared to immediately after a tabletop exercise. Kim [24] reported that competency in disaster nursing significantly increased immediately after a tabletop exercise but showed a decreasing trend after 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…It serves as an interactive learning strategy that promotes student engagement, team building, communication skills practice, and defining roles and responsibilities. 13 Part of the exercise encouraged students to identify resources and call out issues, challenges, and assumptions. Although the design phase of the tabletop simulation was time-intensive, there was no financial cost involved.…”
Section: General Overviewmentioning
confidence: 99%
“…There are many benefits to incorporating a tabletop disaster planning simulation in the classroom. It serves as an interactive learning strategy that promotes student engagement, team building, communication skills practice, and defining roles and responsibilities 13. Part of the exercise encouraged students to identify resources and call out issues, challenges, and assumptions.…”
Section: Tabletop Disaster Planning Exercisementioning
confidence: 99%
“…Then, they prepared a test for these nurses, who had undergone a one-day training, to observe effect of the education on emergency situations. Mirzaei et al ( Mirzaei et al, 2020 ) also made a survey with nurses. They applied a questionnaire to two group of nurses to test whether they were ready for natural disasters.…”
Section: Literature Reviewmentioning
confidence: 99%